Targeted Metabolomics Highlights Dramatic Antioxidant Depletion, Increased Oxidative/Nitrosative Stress and Altered Purine and Pyrimidine Concentrations in Serum of Primary Myelofibrosis Patients - Renata Mangione; Cesarina Giallongo; Andrea Duminuco; Enrico La Spina; Lucia Longhitano; Sebastiano Giallongo; Daniele Tibullo; Giuseppe Lazzarino; Miriam Wissam Saab; Arianna Sbriglione; Giuseppe A. Palumbo; Andrea Graziani; et al. (Antioxidants, 2024)
To date, little is known concerning the circulating levels of biochemically relevant metabolites (antioxidants, oxidative/nitrosative stress biomarkers, purines, and pyrimidines) in patients with primary myelofibrosis (PMF), a rare form of myeloproliferative tumor causing a dramatic decrease in erythropoiesis and angiogenesis. In this study, using a targeted metabolomic approach, serum samples of 22 PMF patients and of 22 control healthy donors were analyzed to quantify the circulating concentrations of hypoxanthine, xanthine, uric acid (as representative purines), uracil, β-pseudouridine, uridine (as representative pyrimidines), reduced glutathione (GSH), ascorbic acid (as two of the main water-soluble antioxidants), malondialdehyde, nitrite, nitrate (as oxidative/nitrosative stress biomarkers) and creatinine, using well-established HPLC method for their determination. Results showed that PMF patients have dramatic depletions of both ascorbic acid and GSH (37.3- and 3.81-times lower circulating concentrations, respectively, than those recorded in healthy controls, p < 0.0001), accompanied by significant increases in malondialdehyde (MDA) and nitrite + nitrate (4.73- and 1.66-times higher circulating concentrations, respectively, than those recorded in healthy controls, p < 0.0001). Additionally, PMF patients have remarkable alterations of circulating purines, pyrimidines, and creatinine, suggesting potential mitochondrial dysfunctions causing energy metabolism imbalance and consequent increases in these cell energy-related compounds. Overall, these results, besides evidencing previously unknown serum metabolic alterations in PMF patients, suggest that the determination of serum levels of the aforementioned compounds may be useful to evaluate PMF patients on hospital admission for adjunctive therapies aimed at recovering their correct antioxidant status, as well as to monitor patients’ status and potential pharmacological treatments.